Challenging the monolingual mindset: language teachers’ pushback and enactment of critical multilingual language awareness in Australian schools - Vellz, Leonardo; Chen, Julian (Taylor & Francis, 2024)
This study critically interrogates dominant discourses and practices in school settings, which reveal the legitimisation and perpetuation of a monolingual mindset. Through the lens of ‘Critical Multilingual Language Awareness’ (CMLA), this research unpacked the experiences and practices of language teachers who implement the New South Wales (NSW) mandated language curriculum and, where possible, create opportunities for adjustments to language syllabi for greater awareness of diversity and plurilingualism. Data was gathered through in-depth semi-structured interviews with four high-school language teachers at independent schools in NSW, Australia. The interview addressed teachers’ proficiency and knowledge of subject matter, their views of the (im)possibilities of the NSW language curriculum for developing plurilingual learners, and perceived challenges that appear to prevent multi/plurilingualism from being at the forefront of Australian language education. Findings revealed that despite teachers’ strong commitment to languages education, they feel discouraged about the limited focus at national and State government levels on consistent and systematic multilingual education. This not only diminishes every effort made by teachers to transform pedagogies for pedagogies for multilingualism but also legitimises a dominant underlying rhetoric of monolingualism that does not adhere to the principles of educating for democratic citizenship.